Makna Gramatikal dan Leksikal pada Lirik Lagu Sialan Karya Andrian Khalif - Saputri, Pramita Yun; Wahyono, Hari (UPA Bahasa Universitas Tidar And HISKI Kedu, 2025)
This research aims to analyze the grammatical and lexical meaning of the lyrics of the song